The Relationship between Junk Food Consumption and the Incidence of Depression in the Faculty of Medicine, Ciputra University, Surabaya - Angeline, Priscilla; Wartiningsih, Minarni (Dian Nuswantoro Semarang, 2023)
Junk food refers to either food or drink that has been processed and is ready to be served on an order basis. In Indonesia, especially at urban areas junk food could easily to be found and accessed by public. Students tends to consume junk food as they have the speed, hygiene, accessability, affordability, taste, and prestige. Previous studies have shown a positive relationship between junk food consumption and the incidence of depression. The purpose of this study was to determine the correlation between junk food consumption and the incidence of depression in students of the Faculty of Medicine at Ciputra University of Surabaya. This research is an observational analitic study. In this study, 73 samples were taken from students of the Faculty of Medicine at Ciputra University of Surabaya (2018, 2019, 2020, and 2021 batch). Research data was processed using the Spearman Rank Test. Results showed that there was no significant correlation between junk food consumption and the incidence of depression in students of the Faculty of Medicine at Ciputra University of Surabaya, which may be related to the time when the research data was collected, namely the COVID-19 pandemic era. It is hiped that people will still maintain a healthy lifestyle by avoiding the consumption od junk food as there are still negative impacts for health by consuming it.